Difference in space‐charge recombination of proton and electron irradiated GaAs solar cells. (7th February 2019) - Pellegrino, Carmine; Gagliardi, Alessio; Zimmermann, Claus G.
Abstract: GaAs component cells, representative of the middle cell in Ga0.5 In0.5 P/GaAs/Ge triple junction solar cells, were irradiated with protons and electrons of various energies and fluences. The local ideality factor, calculated from the measured dark J‐V curves, exhibits a characteristic signature of the irradiating particle. With the help of an analytical model based on Shockley‐Read‐Hall statistics, the recombination current in the space‐charge region is calculated, and the local diode ideality factor is reproduced accurately. The inclusion of defect levels away from the intrinsic Fermi level in the bandgap is found to be essential, since a classical two‐diode model fails to describe the experimental data. On the basis of literature data of known defect levels in irradiated GaAs, the associated lifetimes and defect introduction rates are derived. Abstract : The same nonionizing dose deposited either by protons or by electrons in GaAs solar cells affects the recombination current originating from the space‐charge region differently. An analytical approach based on Shockley‐Read‐Hall statistics is able to model the dark current and the local diode ideality factor, thereby avoiding an unphysical exponent n, 1 < n < 2. Moreover, based on literature data of known defect levels in irradiated GaAs, the associated lifetimes and defect introduction rates are derived.